Several analyses of Chinese manufacturing entrepreneurs' enterprise performance improvement through information sharing - Hu Mengting; Noor Fzlinda Fabeil; Ang Hong Loong (Human Resource Management Academic Research Society, 2024)
With rapid changes in the external environment, it is increasingly difficult for enterprises to survive alone. Scholars now focus on the impact of inter-organizational relationships and networks on corporate performance. Enterprises must manage networks effectively, making the study of network capability and corporate performance crucial. Hakansson introduced network capability in 1987, and many scholars have since defined and modeled it, exploring its link to corporate performance. However, network capability is still emerging, particularly in China, where research is nascent and lacks diverse perspectives and empirical testing.This study, based on Chinese manufacturing enterprises and literature review, redefines network capability's conceptual model, proposes a framework for improving corporate performance, and empirically tests the relationships among variables.